Peripheral extent of the choroidal circulation by ultra-widefield indocyanine green angiography in healthy eyes. Issue 6 (22nd August 2020) - Verma, Aditya; Maram, Jyotsna; Alagorie, Ahmed Roshdy; van Hemert, Jano; Bell, Darren J; Singer, Michael; Keane, Dana; Carnevale, Jessica; Nittala, Muneeswar; Sadda, SriniVas
Abstract : Aim: To analyse the peripheral extent of choroidal circulation using ultra-widefield (UWF) indocyanine green angiography (ICGA) in healthy eyes. Methods: UWF ICGA images of 55 eyes of 36 healthy subjects were captured using the Optos California (Optos, Dunfermline, United Kingdom) in this prospective observational study. Images were analysed to locate the peripheral extent of the visible choroidal circulation, and the boundary was marked in ImageJ (v1.52). Each pixel annotated as the border of the choroidal circulation was projected individually to its anatomically correct location on the three-dimensional model eye, and spherical trigonometry was applied (using the Optos software) to calculate its respective radial distance from the centre of the optic disc in metric units (corrected by stereographic projection) for each quadrant. Results: The mean area of the peripheral extent was estimated to be 893.2 mm 2 (95% CI: 844.2 to 942.3 mm 2 ). The mean distance (range) of this boundary from optic nerve centre was 18.22 mm (95% CI: 14.0 to 23.14 mm). Multiple regression analysis with age, gender, axial length or ethnicity showed no relationship. There was excellent inter-grader reproducibility, with intraclass correlation coefficients of 0.95 (95% CI: 0.80 to 0.99, p <0.001) for distance and 0.99 (95% CI: 0.988 to 0.999, p <0.001) for area measurements. Conclusions: The peripheral choroidal boundary may be defined using UWF ICGA. Knowledge of the normal extent and its variability is essential to understand the impact of disease on the choroidal vasculature.